Relationship Between Contact Force Sensing Technology and Medium‐Term Outcome of Atrial Fibrillation Ablation: A Multicenter Study of 600 Patients. (11th February 2015) - JARMAN, JULIAN W.E.; PANIKKER, SANDEEP; DAS, MOLOY; WYNN, GARETH J.; ULLAH, WAQAS; KONTOGEORGIS, ANDRIANOS; HALDAR, SHOUVIK K.; PATEL, PREYA J.; HUSSAIN, WAJID; MARKIDES, VIAS; GUPTA, DHIRAJ; SCHILLING, RICHARD J.; et al.
Contact Force Sensing AF Ablation Outcomes Introduction Contact force sensing (CFS) technology improves acute pulmonary vein isolation durability; however, its impact on the clinical outcome of ablating atrial fibrillation (AF) is unknown. Methods and Results First time AF ablation procedures employing CFS from 4 centers were matched retrospectively to those without CFS in a 1:2 manner by type of AF. Freedom from atrial tachyarrhythmia was defined as the primary outcome measure, and fluoroscopy time the secondary outcome measure. Nineteen possible explanatory variables were tested in addition to CFS. A total of 600 AF ablation procedures (200 using CFS and 400 using non‐CFS catheters) performed between 2010 and 2012 (46% paroxysmal, 36% persistent, 18% long‐lasting persistent) were analyzed. The mean follow‐up duration was 11.4 ± 4.7 months—paroxysmal AF 11.2 ± 4.1 CFS versus 11.3 ± 3.9 non‐CFS (P = 0.745)—nonparoxysmal AF 10.4 ± 4.5 CFS versus 11.9 ± 5.4 non‐CFS (P = 0.015). The use of a CFS catheter independently predicted clinical success in ablating paroxysmal AF (HR 2.24 [95% CIs 1.29–3.90]; P = 0.004), but not nonparoxysmal AF (HR 0.73 [0.41–1.30]; P = 0.289) in a multivariate analysis that included follow‐up duration. Among all cases, the use of CFS catheters was associated with reduced fluoroscopy time in multivariate analysis (reduction by 7.7 [5.0–10.5] minutes; P < 0.001). Complication rates were similar in both groups. Conclusions At medium‐term follow‐up, CFS catheter technology is associated with significantly improved outcome of first time catheter ablation of paroxysmal AF, but not nonparoxysmal AF. Fluoroscopy time was lower when CFS technology was employed in all types of AF ablation procedures.